Răspuns :
a+b+c = 2.450;
a = 250 + b;
a = 180 + c;
Atunci, b = a - 250 si c = a - 180; le inlocuiesti in prima ecuatie si obtii asa:
3a - 430 = 2.450 => 3a = 2.880 => a = 960 => b = 710 si c = 780.
Bafta!
a = 250 + b;
a = 180 + c;
Atunci, b = a - 250 si c = a - 180; le inlocuiesti in prima ecuatie si obtii asa:
3a - 430 = 2.450 => 3a = 2.880 => a = 960 => b = 710 si c = 780.
Bafta!
A=250+B B=A-250
A=180+C C=A-180
A+B+C=A+ A-250+ A-180=3A-430=2450
3A=2450+430=2880 A=2880/3=960
A=960
B=710
C=780
A=180+C C=A-180
A+B+C=A+ A-250+ A-180=3A-430=2450
3A=2450+430=2880 A=2880/3=960
A=960
B=710
C=780